METODE PENDIDIKAN ISLAM KACAMATA HASAN AL — BANNA - M Riza Zainuddin (IMTIYAZ: Jurnal Ilmu Keislaman, 2021)
AbstractEducation is very closely related to the factors of change in the culture of human life. There needs to be improvements in every educational process to be able to formulate a good and decent life in accordance with expectations. The task of education to have strategic potential has a role in bringing a superior foundation in facing the threat of future challenges that have a dynamic nature. Education should be able to face the era of modernization to balance or face the waves of change. Therefore, major problems arise regarding the concept of Islamic education methods that currently need to be studied and explored. Judging from the history of civilization, Islamic education has existed since the time of the Prophet Muhammad who continues to develop to face the challenges of the modernization era, but the current reality of Islamic education has not been able to face the challenges of the times for the current era. Therefore, the main problem in this study is how is the method of Islamic education in the perspective of Hasan Al-Banna? This research proves that the method of Islamic religious education initiated by Hasan Al-Banna is proven to be able to face the challenges of modernization of the times.